2-chloro-1-(3-methyl-3-phenylcyclobutyl)ethanone - Dincer, Muharrem; Ozdemir, Namik; Yilmaz, Ibrahim; Buyukgungor, Orhan (Int Union Crystallography, 2007)
The title compound, C13H15ClO, has a nonplanar conformation. The phenyl ring and chloroacetaldehyde group are in cis positions. Molecules are linked to one another by intermolecular C-H center dot center dot center dot O interactions, forming a C(4) chain running parallel to the [001] direction. The cyclobutane ring is puckered, with a dihedral angle of 26.81 (13)degrees.